2003
DOI: 10.1098/rspa.2002.1044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermo– and diffusiophoretic forces on the motion of flame-generated particles in the neighbourhood of burning droplets in microgravity conditions

Abstract: Numerical analysis of the e¬ect of thermo-and di¬usiophoretic forces on the motion of moderately large (0:01 . Kn . 0:3) combustion-generated (soot) particles and on the formation of soot-shell structure in the buoyancy-free spherical droplet ®ames is performed. Transient evaporation, ignition and combustion of a single sootingfuel droplet immersed into a quiescent hot environment are considered, taking into account the e¬ects of radiative heat losses, variable transport properties and the dependence of the dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 50 publications
(73 reference statements)
1
10
0
Order By: Relevance
“…(3) Finally, as the viscous shell inhibits vaporization, the flame moves closer to the surface (contraction), heating up the shell quickly beyond the heterogeneous nucleation temperature of xylene and 2-EH acid, initiating disruptions. Moreover, disruptions are only observed if Sn(II)2-EH is present, coinciding with the observations of Wong et al 73,74 and Byun et al 75 In addition, the disruption may also be initiated by soot or nanoparticles, which are formed in the flame and transported back to the droplet by thermophoresis as proposed by Shaw et al 31 Very small particles (d p 200 nm ) from the gas phase can get close to the droplet surface, as was shown by Ben-Dor et al 76 The probability of such an effect may increase as the flame contracts due to a decreasing vaporization rate ( Figure S1 of Supporting Information), thus reducing the force (i.e., drag force due to the Stefan flow) counteracting thermophoresis. Entrapped ambient gas ( Figure 9) may also draw particles into the liquid, where they can act as nuclei.…”
Section: Decomposition During Combustion Of Binary Xylene/ Metal-2-ehsupporting
confidence: 76%
“…(3) Finally, as the viscous shell inhibits vaporization, the flame moves closer to the surface (contraction), heating up the shell quickly beyond the heterogeneous nucleation temperature of xylene and 2-EH acid, initiating disruptions. Moreover, disruptions are only observed if Sn(II)2-EH is present, coinciding with the observations of Wong et al 73,74 and Byun et al 75 In addition, the disruption may also be initiated by soot or nanoparticles, which are formed in the flame and transported back to the droplet by thermophoresis as proposed by Shaw et al 31 Very small particles (d p 200 nm ) from the gas phase can get close to the droplet surface, as was shown by Ben-Dor et al 76 The probability of such an effect may increase as the flame contracts due to a decreasing vaporization rate ( Figure S1 of Supporting Information), thus reducing the force (i.e., drag force due to the Stefan flow) counteracting thermophoresis. Entrapped ambient gas ( Figure 9) may also draw particles into the liquid, where they can act as nuclei.…”
Section: Decomposition During Combustion Of Binary Xylene/ Metal-2-ehsupporting
confidence: 76%
“…The data show that the SSR increases with increasing D o for the three alkanes. Though no theory currently exists for droplet burning that incorporates soot formation, prior qualitative modeling and scaling has shown that forces due to thermophoresis and drag (associated with fuel evaporation) are the dominant influences on trapping soot aggregates between the droplet and flame [3,12,15] . As such, viewing the thermophoretic forces on aggregates entirely from the perspec- tive of the flame temperature, thermophoresis will decrease with D o because the flame temperature also decreases.…”
Section: Resultsmentioning
confidence: 99%
“…6 a). This asymmetry comes from either early soot shell distortion (due to ISS igniters retraction) or incident soot aggregation at one angle such that it has less physical meaning regarding the position where the soot particles are situated as a result of the "force balance" between Stefan drag, diffusio-phoresis and thermophoresis [12,54,55] . The non-spherical part of soot shell is therefore excluded and the circle extended around the circumference.…”
Section: Image Analyses and Data Reductionmentioning
confidence: 98%
See 2 more Smart Citations